UPI LABORATORY REGULATION EVALUATION: CASE STUDY AGAINST LABSCHOOL UPI SCHOOL - Prayoga Bestari (Universitas Padjadjaran, 2023)
Management in each laboratory school is different from other schools in general. This research is a description of the policy evaluation on the regulation of laboratory schools that will provide educational services to students as expected (vision and mission of the lab school), become a place for developing various teacher and educational practices in teacher professional education, and a place for the development of various educational innovations. Laboratory schools are places where prospective professional teachers practice and develop educational innovations and act as model schools for creative and innovative learning practices for prospective professional teachers. By using a qualitative approach and a case study method, this study seeks to provide an overview of the laboratory school regulations in UPI. The results showed that, UPI PTNbh already has a special regulation on laboratory school governance, namely Rector Regulation No.4439 / UN40 / HK / 2019 concerning UPI School Organizing Bodies. Management of educational units at a certain level by educational units at other levels, needs to be affirmed by strong rules and needs to be operated effectively. Good and fair which is reflected in the dynamics of management, there is a proportional distribution of authority and a strategic distribution of power. The strategic division of power is characterized by the sharing of legal powers that are binding and obeyed which do not create multiple perceptions and harm the community using education.